The effect of ethanol on hydroxyl and carbonyl groups in biopolyol produced by hydrothermal liquefaction of loblolly pine: 31P-NMR and 19F-NMR analysis. (August 2016) - Celikbag, Yusuf; Via, Brian K.; Adhikari, Sushil; Buschle-Diller, Gisela; Auad, Maria L.
Highlights: For the first time, 31 P-NMR and 19 F-NMR were employed to understand the effect of ethanol on the formation bio-oil. Ethanol significantly increased the bio-oil and decreased the residue yield. Addition of ethanol increased the hydroxyl concentration while decreased the carbonyl concentration. More aliphatic and less phenolic type OH was obtained when ethanol was used as a co-solvent. Abstract: The goal of this study was to investigate the role of ethanol and temperature on the hydroxyl and carbonyl groups in biopolyol produced from hydrothermal liquefaction of loblolly pine ( Pinus spp.) carried out at 250, 300, 350 and 390 °C for 30 min. Water and water/ethanol mixture (1/1, wt/wt) were used as liquefying solvent in the HTL experiments. HTL in water and water/ethanol is donated as W-HTL and W/E-HTL, respectively. It was found that 300 °C and water/ethanol solvent was the optimum liquefaction temperature and solvent, yielding up to 68.1 wt.% bio-oil and 2.4 wt.% solid residue. 31 P-NMR analysis showed that biopolyol produced by W-HTL was rich in phenolic OH while W/E-HTL produced more aliphatic OH rich biopolyols. Moreover, biopolyols with higher hydroxyl concentration were produced by W/E-HTL. Carbonyl groups were analyzed by 19 F-NMR, which showed that ethanol reduced the concentration of carbonyl groups.